2011
DOI: 10.1038/ncomms1179
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal UBA domains protect ubiquitin receptors by preventing initiation of protein degradation

Abstract: The ubiquitin receptors Rad23 and Dsk2 deliver polyubiquitylated substrates to the proteasome for destruction. The C-terminal ubiquitin-associated (UBA) domain of Rad23 functions as a cis-acting stabilization signal that protects this protein from proteasomal degradation. Here, we provide evidence that the C-terminal UBA domains guard ubiquitin receptors from destruction by preventing initiation of degradation at the proteasome. We show that introduction of unstructured polypeptides that are sufficiently long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 44 publications
4
52
0
Order By: Relevance
“…Such an auto-inhibitory mechanism has been concluded for another DUB, USP4, also with an embedded UBL domain that can compete with substrate by acting as a ubiquitin mimic at the catalytic site (74,75). A somewhat similar model implied conformational changes related to the UBL domain of other UDPs upon proteasome incorporation (76,77). However, as this study observed Ubp6 lacking UBL incorporated into proteasomes, such confrontational changes are probably more subtle and do not necessitate the UBL domain for activation.…”
Section: Rpn1 Differentiates Between Ubiquitin and Ubiquitin-likementioning
confidence: 47%
“…Such an auto-inhibitory mechanism has been concluded for another DUB, USP4, also with an embedded UBL domain that can compete with substrate by acting as a ubiquitin mimic at the catalytic site (74,75). A somewhat similar model implied conformational changes related to the UBL domain of other UDPs upon proteasome incorporation (76,77). However, as this study observed Ubp6 lacking UBL incorporated into proteasomes, such confrontational changes are probably more subtle and do not necessitate the UBL domain for activation.…”
Section: Rpn1 Differentiates Between Ubiquitin and Ubiquitin-likementioning
confidence: 47%
“…As described below, Rad23 participates in the nucleotide excision repair (NER) pathway of DNA repair. Finally, mutated variants of the shuttling receptors have been studied as unique model substrates of the proteasome, although their wild-type forms are relatively stable (Heessen et al 2005;Fishbain et al 2011;Heinen et al 2011;Sekiguchi et al 2011) Deubiquitylation at the proteasome: The lid is positioned for the most part laterally to the base, and its subunits extend like fingers to contact the base at many points ( Figure 5C; Lander et al 2012;Lasker et al 2012). A key function of the lid is to deubiquitylate proteasome substrates, an activity mediated by its subunit Rpn11 (Maytal-Kivity et al 2002;Verma et al 2002;Yao and Cohen 2002).…”
Section: Regulatory Particlementioning
confidence: 99%
“…These proteins bind to the proteasome through their UbL (ubiquitin-like) domains and to ubiquitinated proteins through their UBA (ubiquitin associated) domains and stimulate degradation of the ubiquitinated protein while the UbL-UBA proteins themselves escape degradation. The mechanism behind this unexpected stability of UbL proteins has been investigated for yeast Rad23 [59-61]. These experiments showed that Rad23 escapes degradation because it lacks an effective proteasome initiation site [60,61].…”
Section: A Second Component To the Proteasome Targeting Code?mentioning
confidence: 99%
“…The mechanism behind this unexpected stability of UbL proteins has been investigated for yeast Rad23 [59-61]. These experiments showed that Rad23 escapes degradation because it lacks an effective proteasome initiation site [60,61]. …”
Section: A Second Component To the Proteasome Targeting Code?mentioning
confidence: 99%